ANALISIS STRATEGI DAN METODE PEMBELAJARAN PKN DI SEKOLAH DASAR - Karima, Muhammad Kaulan; Adha, Muhammad Mona; Putri, Risna Estuning; Hendra, Putra You; Rahayu, Salamah Tri; Safitri, Lauressya Mega; Afriyani, Qonita; Saputra, Jufri; Aryandi, Andi (LPPM UM Metro, 2024)
This study analyzes the strategies and methods of teaching Civic Education (PKn) in elementary schools, focusing on their characteristics, effectiveness, and relevance to improving student learning outcomes. Through a literature review, this research identifies various strategies such as expository, discovery, inquiry, problem-based, and contextual approaches, alongside methods including lectures, discussions, question-and-answer sessions, and demonstrations. Each approach is examined based on its contribution to interactive, participatory, and value-based learning. Furthermore, this study highlights the underlying learning theories constructivism, behaviorism, social learning, humanism, and cognitivism that inform the application of these strategies and methods. Findings indicate that consensus-based learning in Grade VI can enhance critical thinking skills and student participation through contextual strategies, discussions, and simulations. By linking learning materials to real-life experiences, this study emphasizes the importance of aligning strategies and methods to support the holistic development of students' civic character. The research offers recommendations for developing innovative and relevant PKn teaching approaches tailored to the demands of 21st-century education.